Degradation of an oncology drugs by heterogeneous photocatalysis using (g-C3N4) on a fiberglass substrate - Chávez Mero, María Fernanda (2025)
Imatinib mesylate (IMB) is a cytotoxic drug found in hospital wastewater, rivers, and other water bodies, posing a significant risk to the ecological balance of aquatic ecosystems. This study evaluates the feasibility of removing and mineralizing IMB through heterogeneous photocatalysis as an environmentally sustainable alternative to traditional treatment methods. Graphitic carbon nitride immobilized on fiberglass (g-C3N4@FV) was used as a photocatalyst under UV irradiation, assisted by hydrogen peroxide (H₂O₂) at a concentration of 1 mmol/50 mL. Experimental tests were conducted using water samples contaminated with 10 mg/L of IMB, subjected to different treatments: photolysis, H₂O₂-assisted photolysis, and complete photocatalysis. Results showed an 87.17% degradation using free g-C3N4 and 51.63% with g-C3N4@FV within 60 minutes, along with a 52.20% reduction in chemical oxygen demand (COD). The biodegradability index of the treated effluent reached a value of 0.54, highlighting the potential of this technique as an efficient alternative for the environmental management of pharmaceutical-contaminated effluents.